2006
DOI: 10.1055/s-2005-872867
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Immunohistochemical Detection of Positive Lymph Nodes in Early Stage Lung Cancer

Abstract: Our study provides some indication that patients with lymphatic micrometastasis have a reduced DFS. Before creating a new TNM staging system, more information is needed to understand the prognostic impact of micrometastatic dissemination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Some authors have reported a significant impact of micrometastasis on prognosis. 18,19 The prognostic value of IHC-detected micrometastasis has been shown in cancers of the breast and lung, 20,21 and this encouraged us and others to evaluate its use in EC. Prenzel et al reported that patients with clinical response following neoadjuvant chemoradiation had significantly fewer lymph node micrometastases.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported a significant impact of micrometastasis on prognosis. 18,19 The prognostic value of IHC-detected micrometastasis has been shown in cancers of the breast and lung, 20,21 and this encouraged us and others to evaluate its use in EC. Prenzel et al reported that patients with clinical response following neoadjuvant chemoradiation had significantly fewer lymph node micrometastases.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 43 articles, 10 presented insufficient information for extracting HRs, 5 not exclusively recruiting pN 0 patients (14-18). Moreover, 7 studies enrolled less than 10 cases in the OTC group (19)(20)(21)(22)(23)(24)(25). Two duplicated articles (26,27) with the same authors were less informative than 2 enrolled articles (7,28).…”
Section: Resultsmentioning
confidence: 99%
“…While some authors have indicated that the presence of micrometastasis or ITC does not affect the postoperative survival of NSCLC patients, 8 many investigators have reported that the survival of NSCLC patients with micrometastasis or ITC is poorer than that of NSCLC patients without micrometastasis or ITC. 5,6 The clinical significance of distinguishing between micrometastasis and ITC in NSCLC has yet to be established. 9 Because of their unclear clinical significance, we now have a policy to carry out completion lobectomy, even a few days after segmentectomy, in patients with micrometastasis or ITC in lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have reported that IHC or reverse transcription polymerase chain reaction (RT-PCR) can determine the presence of microscopic metastasis in 16-28% of NSCLC patients in the p-N0 stage. 5,6 However, it is almost impossible to examine all dissected lymph nodes with IHC and/or RT-PCR. Because SNs have a greater likelihood of developing metastases than non-SNs, we believe that SN identification could target the lymph nodes to determine the presence of micrometastasis using several step sections, IHC, and/or RT-PCR.…”
Section: Discussionmentioning
confidence: 99%